2018
DOI: 10.1186/s12955-018-0999-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life measures and health utility values among dry eye subgroups

Abstract: BackgroundTo determine whether quality of life (QOL) and health utility are affected to the same extent among dry eye (DE) patients with short tear film break-up time dry eye (TBUT-DE) with minimal clinical signs were as severe as aqueous-deficient dry eye (ADDE).MethodsA multicenter cross-sectional study was conducted among DE patients who visited one of 10 eye clinics in Japan. Among the 463 registered patients, this study involved 449 patients with DE who were aged 20 years or older. Ophthalmic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…We collected data from the DECS-J, which was a cross-sectional observational study conducted at 10 eye clinics in Japan [ 6 , 18 , 19 ]. All investigators at the study sites were specialists in ocular surface disorders and DED and belonged to the Japanese Dry Eye Society.…”
Section: Methodsmentioning
confidence: 99%
“…We collected data from the DECS-J, which was a cross-sectional observational study conducted at 10 eye clinics in Japan [ 6 , 18 , 19 ]. All investigators at the study sites were specialists in ocular surface disorders and DED and belonged to the Japanese Dry Eye Society.…”
Section: Methodsmentioning
confidence: 99%
“…Attribute levels of 1 indicate normal/no impairment with increasing values reflecting increased impairment. The validity and reliability of the HUI system has been demonstrated in multiple languages, populations and across disease states …”
Section: Methodsmentioning
confidence: 99%
“…Dry eye disease is accompanied by negative health-related quality of life consequences 47 with a significant impact on the symptoms of depression. 48 Shigeyasu and coauthors reported a significant reduction in quality-of-life in Japanese dry eye patients 31 and, vision-related quality-of-life was found to be impaired in Chinese dry eye patients as well as being also correlated with anxiety and depression. 49 While the consequences of reduced quality of life in dry eye patients can include mood alterations, depression and anxiety, 50 similarly dry eye disease is prevalent in patients with depressive and anxiety disorders, especially for patients who are older, have longer duration of psychiatric disorder, and who use a selective serotonin reuptake inhibitor.…”
Section: Quality Of Life and Dry Eye Syndromesmentioning
confidence: 99%
“… 30 Patients with contributions to their symptoms from both neuropathic and tear dysfunction mechanisms might be the most confusing and difficult to help. There is no drug targeting neuropathic pain 31 but maintenance of optimum tear homeostasis and avoidance of harsh environments which challenge tear functions, may aid repair of any corneal nerve damage.…”
Section: Symptoms Involving Neuropathic Painmentioning
confidence: 99%